MHD heat and MASS transfer of jet nanofluids flow on the porous wall with chemical reaction - Mohd Zailani, Natasha Amira (2018)
The enhancement of heat and mass transfer of jet flow of nanofluids over a porous wall with chemical reaction effects is numerically studied using different types of nanoparticles such as copper (Cu), alumina ( 2 3 Al O ), and single wall carbon nanotubes (SWCNTs) with water as the base fluid. The similarity transforms represented as the jet flow of the nanofluids with the important influences of different flow physical parameters such as magnetic field parameter, heat source parameter, nanoparticles volume fraction parameter, thermal radiation parameter, chemical reaction parameter, Schmidt number parameter, Brownian motion parameter, and thermophoresis parameter. The boundary layer approximation is used to convert governing equations into ordinary differential equations with the boundary conditions. The obtained equations are solved by using Fourth-fifth order Rung-Kutta Fehlberg numerical method with shooting method. It has been studied by the effect of all parameters involved that the heat transfer rate of SWCNTs-water is higher than 2 3 Al O -water and Cu-water whereas the mass transfer rate of Cu-water is higher than SWCNTs-water and 2 3 Al O -water. Furthermore, as the heat source increases, the boundary layer degenerates energy which causes the rate of heat transfer for SWCNTs-water, Cuwater, and 2 3 Al O -water to decrease whereas the rate of mass transfer for all nanoparticles involved also decrease. It is found that the chemical reactions happen at a characteristic reaction rate at given temperature and chemical concentration. Thus, increase in temperature of the reaction gives the molecules more kinetic energy to move faster (collide) and react between nanofluids.